Biofunctional scaffolds with high packing density of aligned electrospun fibers support neural regeneration - Cnops, Vanja (2020)
Neurons of the central nervous system do not regenerate spontaneously after injury. As such, biofunctional tissue scaffolds have been explored to provide a growth‐promoting environment to enhance neural regeneration. In this regard, aligned electrospun fibers have proven invaluable for regeneration by offering guidance for axons to cross the injury site. However, a high fiber density could potentially limit axonal ingrowth into the scaffold. Here, we explore which fiber density provides the optimal environment for neurons to regenerate. By changing fiber electrospinning time, we generated scaffolds with different fiber densities and implanted these in a rat model of spinal cord injury (SCI). We found that neurons were able to grow efficiently into scaffolds with high fiber density, even if the gaps between fiber bundles were very small (<1 μm). Scaffolds with high fiber density showed good host‐implant integration. Cell infiltration was not affected by fiber density. Efficient blood vessel ingrowth likely requires larger gaps between fibers or faster degrading fibers. We conclude that scaffolds with high fiber densities, and thus a large number of small gaps in between fiber bundles, provide the preferred environment for nerve regeneration after SCI.